Online esports competitive team finder web app with built-in tournament creator, custom lobby match-up and profile ratings based on participations and compliments - Yee, Zi Yang (2022)

(untitled)
This is a web application development project for academic purposes. The following proposal project title is to provide students or those who are not familiar with the concept of competitive gaming scene with the history of Esports and its associated competitive options. The proposed project title also provides several solutions to the underlying problems that are faced in the current competitive gaming scene involving around the hassle of finding a team or matchmaking, flexibility of lobby making and tournament hosting and also the problem of player toxicity. The proposed solution and the work done that revolves around the aforementioned problem would be providing a platform for players for the sole purposes of team building across multiple games and regions, other than that, a customizable lobby and tournament would also be viable. To tackle the problem of human nature, hence toxicity, one of the solutions is to introduce a rating system that is calculated based on the players’ participation in lobbies or tournaments and also compliments from other players.